Impact of antibiotic use on patient-level risk of death in 36 million hospital admissions in England. Issue 3 (March 2022) - Budgell, Eric P; Davies, Timothy J; Donker, Tjibbe; Hopkins, Susan; Wyllie, David H; Peto, Tim E A; Gill, Martin J; Llewelyn, Martin J; Walker, A Sarah
Highlights: English hospitals seek 1% annual reductions in their antibiotic use. Antibiotic use per occupied bed-day at english hospitals varies by up to 15-fold. Adjusting for case-mix, this does not impact on mortality risk for medical patients. High antibiotic-using hospitals could be safely benchmarked against low users. Benchmarking against lower-using hospitals could reduce use by up to 1/3. Abstract: Objectives: Initiatives to curb hospital antibiotic use might be associated with harm from under-treatment. We examined the extent to which variation in hospital antibiotic prescribing is associated with mortality risk in acute/general medicine inpatients. Methods: This ecological analysis examined Hospital Episode Statistics from 36, 124, 372 acute/general medicine admissions (≥16y) to 135 acute hospitals in England, 01/April/2010–31/March/2017. Random-effects meta-regression was used to investigate whether heterogeneity in adjusted 30-day mortality was associated with hospital-level antibiotic use, measured in defined-daily-doses (DDD)/1, 000 bed-days. Models also considered DDDs/1, 000 admissions and DDDs for narrow-spectrum/broad-spectrum antibiotics, parenteral/oral, and local interpretations of World Health Organization Access, Watch, and Reserve antibiotics. Results: Hospital-level antibiotic DDDs/1, 000 bed-days varied 15-fold with comparable variation in broad-spectrum, parenteral, and Reserve antibiotic use. After extensive adjusting for hospital case-mix, the probability of 30-day mortality changed -0.010% (95% CI: -0.064, +0.044) for each increase of 500 hospital-level antibiotic DDDs/1, 000 bed-days. Analyses of other metrics of antibiotic use showed no consistent association with mortality risk. Conclusions: We found no evidence that wide variation in hospital antibiotic use is associated with adjusted mortality risk in acute/general medicine inpatients. Using low-prescribing hospitals as benchmarks could help drive safe and substantial reductions in antibiotic consumption of up-to one-third in this population.